Attenuation of E. coli O157:H7 virulence by a combination of natural plant extracts and organic acids before and after refrigerated storage. Issue Volume 1(2019)Issue A (8th March 2019) - Stratakos, Alexandros; Linton, Mark; Ward, Patrick; Sima, Filip; Kelly, Carmel; Pinkerton, Laurette; Gundogdu, Ozan; Corcionivoschi, Nicolae
Abstract : Anti-virulence strategies are an alternative approach to combat zoonotic bacterial pathogens. Although control measures are in place against E. coli O157, it still remains a global health concern with cattle being the most important reservoir. Different feed constituents have varying effects on the virulence of E. coli O157 present in the gut which then are transferred to meat processing surfaces and meat during slaughter. This study explored the anti-virulence properties of a mixture of natural plant extracts and organic acids (citrus, grape and oregano extracts, lactic and citric acid) before and after refrigerated storage as means of reducing the risk from E. coli O157 by reducing its virulence. Assessment of the effects of sub-inhibitory concentrations (0.1 and 0.5 %, v/v) of the antimicrobial mixture before refrigerated storage showed that the pathogen's motility and adhesion onto HCT-8 cells was significantly reduced ( P <0.05) in a dose-dependent manner. Shiga-toxin 2 production was also significantly reduced. Real-time PCR analysis revealed that the mixture of natural antimicrobials repressed expression of adhesion (eae) and shiga-toxin 2 (stx2) genes, which was consistent with the observed reduction in adhesion and toxin production. The same virulence factors were investigated after simulated storage of E. coli O157 in meat simulation medium. Results revealed that after exposure to the antimicrobial mixture, the virulence was significantly lower compared to non-treated control after refrigerated storage. The present work shows the potential of the antimicrobial mixture in reducing virulence and thus risk from E. coli O157 by applying it as a feed additive.